ProMEX – a mass spectral reference database for plant proteomics - Wienkoop, Stefanie; Staudinger, Christiana; Hoehenwarter, Wolfgang; Weckwerth, Wolfram; Egelhofer, Volker (Frontiers in Plant Science, 2012)
The ProMEX database is one of the main collection of annotated tryptic peptides in plant proteomics. The main objective of the ProMEX Database is to provide experimental MS/MS-based information for cell type-specific or subcellular proteomes in Arabidopsis thaliana, Medicago truncatula, Chlamydomonas reinhardtii, Lotus japonicus, Lotus corniculatus, Phaseolus vulgaris, Lycopersicon esculentum, Solanum tuberosum, Nicotiana tabacum, Glycine max, Zea mays, Bradyrhizobium japonicum and Sinorhizobium meliloti. Direct links at the protein level to the most relevant databases are present in ProMEX. Furthermore, the spectral sequence information are linked to their respective pathways and can be viewed in pathway maps.